Gut microbiota and its metabolites in Alzheimer’s disease: from pathogenesis to treatment - Xinfu Zou; Guoqiang Zou; Xinyan Zou; Kangfeng Wang; Zetao Chen (PeerJ, 2024)
Introduction An increasing number of studies have demonstrated that altered microbial diversity and function (such as metabolites), or ecological disorders, regulate bowel–brain axis involvement in the pathophysiologic processes in Alzheimer’s disease (AD). The dysregulation of microbes and their metabolites can be a double-edged sword in AD, presenting the possibility of microbiome-based treatment options. This review describes the link between ecological imbalances and AD, the interactions between AD treatment modalities and the microbiota, and the potential of interventions such as prebiotics, probiotics, synbiotics, fecal microbiota transplantation, and dietary interventions as complementary therapeutic strategies targeting AD pathogenesis and progression. Survey methodology Articles from PubMed and china.com on intestinal flora and AD were summarized to analyze the data and conclusions carefully to ensure the comprehensiveness, completeness, and accuracy of this review. Conclusions Regulating the gut flora ecological balance upregulates neurotrophic factor expression, regulates the microbiota-gut-brain (MGB) axis, and suppresses the inflammatory responses. Based on emerging research, this review explored novel directions for future AD research and clinical interventions, injecting new vitality into microbiota research development.